1986
DOI: 10.1038/320269a0
|View full text |Cite
|
Sign up to set email alerts
|

Pathway selection by growth cones of identified motoneurones in live zebra fish embryos

Abstract: How is the adult pattern of connections between motoneurones and the muscles that they innervate established during vertebrate development? Populations of motoneurones are thought to follow one of two patterns of development: (1) motor axons initially follow stereotyped pathways and project to appropriate regions of the developing muscle or (2) motor axons initially project to some regions that are incorrect, the inappropriate projections being eliminated subsequently. Here we observed individually identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 324 publications
(200 citation statements)
references
References 15 publications
9
190
1
Order By: Relevance
“…Our work is based on the pioneering studies of Eisen, Westerfield and colleagues (Eisen and Meyers, 1986;Meyers et al, 1986Fashena and Westerfield, 1999;Westerfield et al, 1990;Sepich et al, 1998;Liu and Westerfield, 1992). In general, our results are consistent with theirs, but they differ in one respect: they did not observe aneural AChR clusters prior to axon outgrowth or in segments rendered aneural by the ablation of primary motoneurons (Liu and Westerfield, 1992).…”
Section: Discussionsupporting
confidence: 79%
“…Our work is based on the pioneering studies of Eisen, Westerfield and colleagues (Eisen and Meyers, 1986;Meyers et al, 1986Fashena and Westerfield, 1999;Westerfield et al, 1990;Sepich et al, 1998;Liu and Westerfield, 1992). In general, our results are consistent with theirs, but they differ in one respect: they did not observe aneural AChR clusters prior to axon outgrowth or in segments rendered aneural by the ablation of primary motoneurons (Liu and Westerfield, 1992).…”
Section: Discussionsupporting
confidence: 79%
“…By the 14-somite stage (16 hpf), the ventrally located ret1-expressing cells were arranged in a segmental pattern relative to the borders of hemisegments 8 to 20 (2 to 3 ret1 positive cells per hemisegment; Figure 4c). These cells were likely to be primary motor neurons as indicated by their early appearance, ventrolateral location and the relatively large size of their cell bodies (Figure 4b and c; Eisen et al, 1986;Myers et al, 1986;Eisen, 1991). Vital dye labelling and immunohistochemistry using several neuron-speci®c markers, has indicated that three primary motor neurons are present in each hemisegment: the CaP, (Caudal Primary, caudally located); RoP, (Rostral Primary, rostrally located) and MiP, (Middle Primary, between CaP and RoP).…”
Section: Mrna Distribution In the Developing Excretory Systemmentioning
confidence: 99%
“…At 17 hpf, the first wild-type motor growth cones have exited the spinal cord and pioneer a path along the medial surface of the myotome (Bernhardt et al, 1998;Eisen et al, 1986). As pioneering growth cones advance, dense AChR clusters emerge and co-localize along the extending axon, reminiscent of en passant synapses (Fig.…”
Section: Twister-related Phenotypes Are Dependent On Neuromuscular Acmentioning
confidence: 99%